Communicating Higher Education: An Analysis of Journals in the Field of Higher Education - de Gayardon de Fenoyl, Ariane (International Higher Education, 2015)
This article describes the publication landscapes in the field of higher education. Based on a global inventory of journals and publications focused on higher education research, it analyses trends in and draws conclusions on the languages, countries of publication, audience and focus.